P-054 Pre-selected for an award: Apoptosis related-microRNAs in Oligoasthenoteratozoospermia and Azoospermia men may reveal novel study of freezing damage. (6th August 2021) - Ezzati, M; Pashaiasl, M
Abstract: Study question: Could choosing of non-apoptotic spermatozoa by biological biomarkers such as microRNAs promote post-thaw fertilization ability? Summary answer: Biological alterations in correlation with apoptosis and oxidative stress markers such as microRNAs may preserve the function and fertility of spermatozoa during cryopreservation. What is known already: Biological changes of cryopreserved spermatozoa such as microRNAs against cryo-injury were investigated. It was presented that several sperm parameters such as motility and abstinence period can impact the percentage of post-thaw sperm survival. Recent study, reported that microRNAs related to process of motility, sperm structure and apoptosis were associated with different expression after cryopreservation. More comprehensive study needed to fully mention the effect of microRNAs and their correlations with other biomarkers in cryopreservation. Study design, size, duration: Our study was performed on 58 men who were 24-40 years old. Their ejaculated samples were classified as sever (concentrations less than 5 million sperm/mL) Oligoasthenoteratozoospermia (SOAT), mild (concentrations 5 million – 10 million sperm/ mL) Oligoasthenoteratozoospermia (MOAT), obstructive azoospermai (OA), Non obstructive azoospermai (NOA) (absence of spermatozoa in the semen) and normal group (concentrations more than 15 million sperm/ mL). Then each sample was grouped into fresh and cryopreserved one. Participants/materials, setting, methods: Density Gradient centrifugation (DGC) was performed to obtain high quality sperm without round cells after freeze-thawing. Biopsy of testicular tissue was prepared after Testicular Sperm Extraction (TESE) surgery. Then biological biomarkers were examined before and after cryopreservation including microRNA-122 (miR-122), miR-383, miR-15b, miR-184, miR-34c and target genes such as P53, Caspase9 and CYCLIN D1, using Quantitative real-time polymerase chain reaction (RT-PCR). Glutathione peroxidase (GPx), Superoxide dismutase (SOD) and malondialdehyde (MDA) using imaging multi-mode reader. Main results and the role of chance: There was a significant reduction in sperm total motility and morphology in Cryopreserved-infertile groups (MOAT and SOAT) compared with the Fresh-infertile groups. Decreased level of GPx activity was associated with increased concentration of MDA during freeze-thawing procedure in oligoasthenoteratozoospermia. Also increasing levels of SOD, and DNA fragmentation were showed. Our data demonstrated that reduction of CYCLIN D1 in MOAT-Cryopreserved (P = 0.0174) and NOA-Cryopreserved (P = 0.0001) groups were considerable compared with their fresh ones. We observed high level of Capase9 and in cryopreserved groups (P = 0.01).The expression of miR-34c was increased significantly in NOA-Cryo (P = 0.0064), and OA-Cryo (P = 0.0441) in comparison with their fresh groups. The expression of miR-184 (P = 0.0275) was enhanced in NOA-Cryo as compared to NOA-Fresh. Quantitative RT-PCR demonstrated meaningful decrease level of miR-383 expression in SOAT-Cryopreserved as compared with SOAT-Fresh (P = 0.0223). On the other hand, expression level of miR-383 was increased in NOA group significantly (P = 0.0437) and in OA group non-significantly during freezing. There was non-significant decrease of miR-122 and miR-15b in MOAT and SOAT-Cryopreserved groups in comparison to their Fresh groups. We observed reduced expression of miR-122 (P = 0.0109) and miR-15b (P = 0.0322) in OA group after freezing. Also, there was meaningful increased level of miR-15b (P = 0.0234) in NOA-Cryo compared with Fresh.  Limitations, reasons for caution: Because of the ethical principle, we can not obtain testicular samples from normal groups. So, we analyzed NO and OA groups with each other. Wider implications of the findings: Our study documented that total motility can be interfered by microRNAs. This phenomenon effects on the total motility of post-thaw spermatozoa. Also the increase level of MDA may disturb microRNAs regulation in the infertile cases. These non-coding RNAs may be known as fertility biomarker to development of freeze-thawing strategies. Trial registration number: 60961